FARMERS PERCEPTION OF OPPORTUNITIES PREFERENCES AND OBSTACLES OF GROWING MULTIPURPOSE TREES ON FARMLAND IN KOGI STATE - Faith Aladi, Sale; Olagunju John, Olujobi (European Scientific Journal, ESJ, 2014)
A survey was conducted on the present condition of farmlands in Kogi State. Farmers’ knowledge and experience of tree growing, their preferences and perceptions, and obstacles to planting in fifteen villages that form a cross-section of the state geo-political zones. Fifteen household heads were interviewed in each of the fifteen villages. Thus 150 households from the fifteen villages were randomly selected for the study. 150 copies of structured questionnaires were administered to elicit response from the respondents. The survey revealed that almost every farmland contains a combination of different tree species. Farmers generally prefer to grow fruit trees because they can provide income, timber, fuel and fodder for their livestocks. 40% of the respondents are involved in growing of fruit trees for food while 30% grow trees for lumber, 12% and 10% grow trees for fuelwood and environmental protection respectively. Kogi State farmers are aware of the value of multipurpose trees and want to plant more if given the opportunity. Lack of land, technical know – how, inputs, time and labour are major constraints preventing more tree planting. The design of an agroforestry programme to awaken and strengthen extension services and provide seedlings and supports to farmers in Kogi State are recommended.